Hubungan Antara Kecerdasan Spiritual dan Self-Efficacy dengan Kinerja Guru Madrasah Aliyah Al-Fatah Palembang - Nyayu Khodijah; Sukirman S (Universitas Islam Negeri Raden Fatah Palembang, 2014)
Abstract The objective of this study is to find out the characteristics of teacher's performance, spiritual intelligence, and self-efficacy also to find out the correlation between spiritual intelligence, self-efficacy either individually or collectively, and teacher's performance at Madrasah Aliyah Al-Fatah. The descriptive and correlation method was used in this study. The population was teachers at MA Al-Fatah. The total number of respondents was 20. The technique for collecting the data was: psychological scale and questionnaire. The quantitative technique was used to analyze the data. The result of the study shows that: 1) most of the teachers (70) were at fair category based on the performance. 2) most of the teachers (65%) were at fair category based on the spiritual intelligence. 3)  most of the teachers (70%) were at fair category based on the self-efficacy. 4) there were a positive and significant correlation between spiritual intelligence and teacher's performance with contribution of 69.06%. 5) there was no a significant positive and correlation between self-efficacy and teacher's performance with contribution of 17.72%. 6) there were a positive and significant correlation between spiritual intelligence and self-efficacy individually and collectively with contribution of 69.10%.   Keywords: spiritual intelligence, self-efficacy, teacher's performance